Zakat of Business Unions: Towards the Improvement of Concepts and Regulations - Bafadhal, Husin; Rahman, Fuad; Martaliah, Nurfitri (UIN Sunan Kalijaga, 2024)
This article discusses zakat for business associations, which requires refinement of the concept and regulations if it is to be implemented in Indonesia. Although it has been discussed by scholars, how it becomes obligatory, what criteria must be met, and how the provisions of nisab, ḥaul, the obligatory rate, and its implementation are still not receiving significant attention. Furthermore, the lack of clear and comprehensive regulations on zakat for business associations in Indonesia makes this discussion important. Focusing on zakat for business associations, this article will outline the Islamic legal review of zakat for business associations, the provisions of nisab, ḥaul, the obligatory rate, and its implementation. This article is a literature study whose data is processed qualitatively using a normative-comparative approach. After reviewing relevant literature sources, this paper shows that assets in a business association are subject to zakat if they meet the nisab and haul requirements and are paid on behalf of the owners of the associated assets, not on behalf of the business association. Scholars differ in their opinions regarding the nisab requirements for zakat on business partnerships. Some argue that the nisab and haul should be determined based on the business partnership, while others argue that the nisab should be calculated based on the assets of each participant in the business partnership, not the partnership itself. Artikel ini mendiskusikan zakat untuk serikat usaha yang memerlukan penyempurnaan konsep dan regulasi jika diterapkan di Indonesia. Meskipun sudah dibahas oleh para ulama, namun bagaimana ia menjadi wajib, apa kriteria yang harus dipenuhi, serta bagaimana ketentuan nisab, ḥaul, kadar wajib, dan pelaksanaannya, belum mendapatkan perhatian yang berarti. Ditambahkan lagi belum jelas dan tegasnya regulasi zakat serikat usaha di Indonesia yang komprehensif, menjadikan diskusi ini penting untuk dilakukan. Berfokus pada zakat untuk serikat usaha, artikel ini akan menguraikan tinjauan hukum Islam terhadap zakat serikat usaha, ketentuan nisab, ḥaul, kadar wajib, dan pelaksanaannya. Artikel ini merupakan penelitian pustaka yang datanya diolah secara kualitatif menggunakan pendekatan normatif-komparatif. Setelah menelaah sumber-sumber pustaka yang relevan, tulisan ini menunjukkan bahwa harta yang terdapat dalam serikat usaha wajib dikeluarkan zakatnya bila telah memenuhi ketentuan nisab dan hawl dan ditunaikan atas nama pemilik harta yang berserikat, bukan atas nama serikat usaha. Para ulama berbeda pendapat tentang ketentuan nisab zakat serikat usaha. Mereka berpandangan bahwa nisab dan haul dilihat dari serikat usaha dan sebagian berpandangan bahwa perhitungan nisab atas harta masing-masing peserta serikat usaha, bukan pada serikat usaha.